Slack Resources and the Performance of Privately Held Firms - George, Gerard (Academy of Management Journal, 2005)
Empirical findings from publicly traded firms and behavioral arguments suggest a positive influence of resource slack on financial performance. While this area has remained unexplored in privately held firms, conceptual arguments indicate that resource constraints may enhance performance. Longitudinal data on 900 privately held firms confirm the differing influences of forms of slack on performance. Results indicate that a combination of behavioral and resource constraints arguments are necessary to explain the slack-performance relationship in privately held firms. The implications of these findings for theories of resources and entrepreneurship are discussed.